PREVALENCE AND CHARACTERISTICS OF BREAST CANCER IN YOUNG WOMEN - Siregar, Denny Rifsal; Christoper, Andreas (Sumatera Medical Journal, 2020)
Breast cancer is a major health problem for women. This cancer is most often diagnosed and the leading cause of cancer deaths in women worldwide. Breast cancer in young women is associated with late diagnosis, aggressive biological characteristics, and poor prognosis. The objective of the study is to determine the prevalence and characteristics of young age breast cancer in Haji Adam Malik General Hospital Medan in 2013-2017. The study design was observational descriptive design with a cross-sectional approach. The study samples were medical records of young women diagnosed with breast cancer who were treated at Haji Adam Malik General Hospital Medan. The prevalence of breast cancer in young age women in Haji Adam Malik General Hospital Medan in 2013-2017 was 234 patients (15.2%). In this study, the samples that fulfilled the inclusion criteria were 153, with the majority characteristics of patients were 35-39 years old, stage III, histopathological type of invasive carcinoma of no special type, grade II, and clinical subtype of triple-negative. The prevalence of young age breast cancer is lower than old age breast cancer. Young women tend to be diagnosed with breast cancer in advanced stage and intermediate grade with aggressive biological characteristics.